Hypertension and Migraine in the Northern Manhattan Study - Gardener, Hannah (Ethn Dis, 2016)
OBJECTIVE: To investigate the association between migraine and hypertension in the Northern Manhattan Study (NOMAS), a multiethnic community-based sample. DESIGN: Cross-sectional cohort study. PARTICIPANTS: 1338 NOMAS participants (mean age 68.1 ± 9.6 years, 37% male, 15% non-Hispanic White, 19% non-Hispanic Black, 67% Hispanic). SETTING: Northern Manhattan community. INTERVENTION: Participants were assessed for migraine symptoms using a self-report questionnaire based on criteria from the International Classification of Headache Disorders. Hypertension was defined as blood pressure ≥140/90 mm Hg, the patient’s self-reported hypertension, or use of anti-hypertensive medications. Duration (≤9 years vs >9 years) and control (BP<140/90) of hypertension were examined. We estimated the association between hypertension and migraine (overall and with/without aura) using logistic regression, adjusting for sociodemographic and vascular risk factors. RESULTS: The majority of participants (80%) had no migraine, 6% had migraine with aura, and 15% had migraine without aura. Hypertension was present in 76% of the study population (7% had controlled hypertension ≤9 years duration, 5% controlled hypertension >9 years duration, 41% uncontrolled hypertension ≤9 years duration, 23% uncontrolled hypertension >9 years duration). Hypertension was associated with migraine (OR: 1.76, 95% CI: 1.21-2.54), both with and without aura. This association was particularly apparent for those with uncontrolled and long duration hypertension. CONCLUSION: Hypertension, particularly uncontrolled and of long duration, is associated with migraine, both with and without aura, in a predominantly Hispanic community-based cohort.